(untitled) - Soars, John (Thành phố Hồ Chí Minh, 2005)
A multi-level course, supported by a broad range of supplementary material, which targets both accuracy and fluency in all four language skills.
Keywords: Tiếng Anh,English language; Sách giáo khoa cho người nước ngoài,Textbooks for foreign speakers